Expression of TCF3 target genes defines a subclass of diffuse large B-cell lymphoma characterized by up-regulation of MYC target genes and poor clinical outcome following R-CHOP therapy. Issue 1 (2nd January 2023) - Tyryshkin, Kathrin; Moore, Alison; Good, David; Popov, Jesse; Crocker, Susan; Rauh, Michael J.; Baetz, Tara; LeBrun, David P.
Abstract: TCF3 is a lymphopoietic transcription factor that acquires somatic driver mutations in diffuse large B-cell lymphoma (DLBCL). Hypothesizing that expression patterns of TCF3-regulated genes can inform clinical management, we found that unsupervised clustering analysis with 15 TCF3-regulated genes and eight additional ones resolved local DLBCL cases into two main clusters, denoted Groups A and B, of which Group A manifested inferior overall survival (OS, p = 0.0005). We trained a machine learning model to classify samples into the Groups based on expression of the 23 transcripts in an independent validation cohort of 569 R-CHOP-treated DLBCL cases. Group A overlapped with the ABC cell-of-origin subgroup but its prognostic power was superior. GSEA analysis demonstrated asymmetric expression of 30 gene sets between the Groups, pointing to biological differences. We present, validate and make available a novel method to assign DLBCL cases into biologically-distinct groups with divergent OS following R-CHOP therapy.